2020
DOI: 10.1007/s11547-020-01144-8
|View full text |Cite
|
Sign up to set email alerts
|

Direct MR arthrography of the shoulder: current practice in the UK

Abstract: There is wide variation in the technique and type of contrast used for MR arthrography of shoulder. In this article, we discuss the current practice in UK and the reason for the change over the last few years. Keywords Arthrogram • Shoulder • UK Direct MR arthrograms (MRA) utilise distension of the joint capsule to separate intra-capsular structures and hence improve visualisation, when compared to conventional non-arthrographic MRI. Clinical applications of direct MRA were first described in the shoulder, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Anterior instability is one of the most common indications for dMRA [ 174 , 187 ]. One study demonstrated 88% sensitivity, 91% specificity, and 89% accuracy with regard to dMRA and detection of anteroinferior labral tears [ 188 ] (Fig.…”
Section: Joint-specific Indicationsmentioning
confidence: 99%
“…Anterior instability is one of the most common indications for dMRA [ 174 , 187 ]. One study demonstrated 88% sensitivity, 91% specificity, and 89% accuracy with regard to dMRA and detection of anteroinferior labral tears [ 188 ] (Fig.…”
Section: Joint-specific Indicationsmentioning
confidence: 99%
“…Arthrography is an invasive technique of joint evaluation following intra-articular injection of contrast agent or combination of saline &/or local anesthetic 28 to achieve joint distension. Multiplanar fat suppressed T1 weighted image acquisition is performed for MR arthrographic evaluation, if gadolinium based contrast agents are administered.…”
Section: Role Of Arthrography In Cartilage Imagingmentioning
confidence: 99%